1990
DOI: 10.1093/oxfordjournals.eurheartj.a059619
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial, right ventricular and left ventricular thrombi in (incomplete) Behcet's disease

Abstract: An 18-year-old man presented with a history of oral sores and presence of high fever, scrotal ulcerations and haemoptysis. Multiple mural cardiac masses were present in the right atrium, right ventricle and left ventricle. Furthermore, pulmonary vasculitis with aneurysm formation and venous thrombosis involving the superior sagittal sinus and right transverse sinus were found, and the diagnosis was made of (incomplete) Behçet's disease. While receiving anticoagulation and later, treatment with prednisone and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…ICT is located usually in the right side of the heart, the right ventricle being the most common location (6). Involvement of the left heart has been rarely reported (7). In our case series, the right heart was involved in all cases with right ventricular thrombosis in 5 cases and right atrial thrombosis in 3 cases.…”
Section: Casementioning
confidence: 56%
“…ICT is located usually in the right side of the heart, the right ventricle being the most common location (6). Involvement of the left heart has been rarely reported (7). In our case series, the right heart was involved in all cases with right ventricular thrombosis in 5 cases and right atrial thrombosis in 3 cases.…”
Section: Casementioning
confidence: 56%
“…Ozkan et al (6) demonstrated that there is no difference in the prevalence of echocardiographic abnormalities between patients with BD and control subjects. Since the first description by Buge in 1977 (7) up to date, only about 50 cases have been reported (1,2,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Only 10 cases have been reported to date in the English literature. [3][4][5][6][7][8][9][10][11] As well, pulmonary involvement with this disease is rare, with the usual clinical presentation of pulmonary involvement being recurrent massive hemoptysis. 10,12 Repetitive pulmonary embolism has been reported in only 3 cases.…”
Section: Discussionmentioning
confidence: 99%